Clinical review of treatment outcomes and patterns of failure with adjuvant radiotherapy in node‐positive malignant melanoma. Issue 2 (25th September 2016) - Keenan, Lorna G; O'Sullivan, Siobhra; Glynn, Aisling; Higgins, Martin; Flavin, Aileen; Brennan, Sinead
Abstract: Introduction: Adjuvant radiotherapy is proven to prevent lymph node field relapse after therapeutic lymphadenectomy for melanoma, but does not improve overall survival based on current data. There remains a high rate of distant relapse. This study reports patterns of failure in patients treated with adjuvant radiotherapy, looking at factors associated with distant metastasis and comparing this to recent literature. Methods: This retrospective study included patients treated with adjuvant nodal irradiation after lymphadenectomy between June 2012 and March 2015. Results: Twenty‐one patients were treated during this period. Median follow‐up was 13.5 months. There were no lymph node field recurrences. Distant metastasis (DM) rate was 48%. DM rate was significantly higher ( P  = 0.027) in patients with extracapsular extension (ECE) (71%) than those without ECE (0%). DM rate was higher in those with a maximum tumour size of >3 cm (71%) than those with tumour size <3 cm (30%) ( P  = 0.160). Number of nodes, BRAF status or nodal site did not correlate with rate of DM. The median time to DM was 16 weeks after completion of radiotherapy. Conclusion: Radiotherapy is well tolerated and effective in regional control. However, patients are at risk of early distant relapse, particularly those with ECE or large tumour size. There are currently no useful prognostic markers to differentiate the risk of regional versus distant recurrence, and the optimal treatment paradigm remains undefined. Research on adjuvant systemic therapies and abscopal effects of radiotherapy have shown improved management of distant metastasis; creating an even greater need for effective regional control strategies.